Bilingual Education and Arabic Language Learning: A Study of Merdeka Curriculum Practices in Indonesian Madrasah - Zain, Nayla Saada; Inayah, Inayah; Abu Samra, Asma’ Naim Jamil (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aims to explore implementing the Merdeka Curriculum (MC) in Arabic Language Learning (ALL) through the integration of Madrasah Diniyah Khusus (Madinsus) and a bilingual approach at the MTs level within a pesantren environment. Conducted at Pondok Pesantren Modern al-Falah Jatirokeh, Brebes. This field research employed a qualitative descriptive method to explore strategies, challenges, and impacts of curriculum implementation. Data were collected through observation, interviews, and documentation involving selected students from classes VII and VIII, Arabic and Madinsus students, and the school principal. The findings indicate that the integration of Madinsus and the bilingual model supports a more adaptive, contextual, and competence-based Arabic learning experience aligned with 21st-century educational needs. This innovation serves as a strategic effort by the pesantren to adapt to national curriculum reforms without abandoning traditional Islamic values. This study makes an important contribution to the development of Arabic language learning and serves as a model for future Islamic education policies that can harmonize Islamic traditions with the demands of modern competencies.